Unintended Medication Discrepancies (UMD) Pada Saat Rekonsiliasi Transfer dalam Konteks Negara Berpenghasilan Rendah dan Menengah : Tinjauan Naratif - Husain, Aprilia; Khairinisa , Miski Aghnia; Insani , Widya Norma (Journal of Pharmaceutical and Sciences, 2025)
Unintended medication discrepancies (UMD) frequently occur during transitions of care, particularly in low- and middle-income countries (LMICs), where the healthcare system often lacks standardized protocols, integrated information systems, and trained clinical pharmacists. This narrative review aims to explore the prevalence, characteristics, and contributing factors of UMD across LMICs based on analysis of 10 selected studies. Omission was the most frequently reported type of discrepancy, especially among elderly patients with complex therapy regimens. Factors influencing the occurrence of UMD include polypharmacy, inadequate documentation, absence of medication reconciliation protocols, limited pharmacist involvement, and poor inter-facility communication. Despite systemic limitations, studies demonstrate that pharmacist-led interventions can significantly reduce the incidence of UMD, even in resource-limited settings. Comparative analysis with studies from developed countries reveals that digital tools, standardized policies, and integrated pharmacist roles greatly enhance medication safety during transitions of care. The review concludes that addressing UMD in LMICs requires a multi-faceted approach, including national policy development, pharmacist integration into clinical teams, implementation of context-appropriate digital systems, and strengthening pharmacy education. These strategies are crucial for improving patient safety and reducing preventable adverse drug events related to medication discrepancies.